Environmental Aspects of Zoonotic Diseases - Armon, Robert (IWA Publishing, 2012)
Environmental Aspects of Zoonotic Diseases provides a definitive description, commentary and research needs of environmental aspects related to zoonotic diseases. There are many interrelated connections between the environment and zoonotic diseases such as: water, soil, air and agriculture. The book presents investigations of these connections, with specific reference to environmental processes such as: deforestation, floods, draughts, irrigation practices, soil transfer and their impact on bacterial, viral, fungal, and parasitological spread. Environmental aspects such as climate (tropical, sub-tropical, temperate, arid and semi-arid), developed and undeveloped countries, animal traffic animal border crossing, commercial animal trade, transportation, as well geography and weather on zoonosis, are also discussed and relevant scientific data is condensed and organized in order to give a better picture of interrelationship between the environment and current spread of zoonotic diseases.